Comparison Before and After Interest Rate Cut On Bank Profitability Elvi Amira Marsyidaa, - Elvi Amira Marsyida; Muchriana Muchran (www.amertainstitute.com, 2024)
This study examines the difference before and after interest rate cuts on bank profitability. The central bank of the United States (US) The Federal Reserve (The Fed) surprised the world by cutting the benchmark interest rate by 50 basis points (bps) to 4.75%-5.0%. This study was conducted to analyze the difference before and after interest rate cuts on bank profitability. The observation period is the 2nd quarter before and the 3rd quarter after. A bank's profitability is measured by Return On Asset (ROA). The type of quantitative research with the analysis method used is a nonparametric differential test. The sample used is 35 companies registered on the IDX and on the main board. The results of this study show that bank profitability measured by ROA shows a significant difference between before and after the interest rate cut.